TWO-STAGE DECISION-MAKING IN ONLINE FASHION MSMES: AN ISLAMIC MANAGERIAL ECONOMICS PERSPECTIVE IN PEKALONGAN, INDONESIA - Dwi Yoga Prasetyo; Kresna Mustika; Tamamudin; Ali Muhtarom (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to explore and map the strategic decision-making sequences of online fashion MSMEs in Pekalongan through the lens of Islamic managerial economics. It specifically investigates how Islamic ethical constraints, such as the avoidance of gharar (uncertainty) and the pursuit of Siddiq (honesty), reconfigure the cognitive process of choosing between digital platforms and marketing techniques. Following an interpretivist paradigm, this research employed a qualitative multiple-case study design using three distinct cases: a traditional batik artisan, a work trousers manufacturer, and a contemporary jeans retailer. Data were collected through semi-structured interviews using a "stated preference" elicitation technique and triangulated via direct digital observation of the participants' online storefronts. The results identify three distinct decision-tree patterns: lexicographic, nested, and co-lexicographic. The findings suggest and illustrate a concept of sharia-bounded rationality, where for the observed Muslim entrepreneurs, digital choices appear to be governed by ethical parameters such as ensuring transaction transparency and rejecting usurious financial mechanisms (riba) act as the primary filters for commercial viability rather than mere profit maximization. While providing deep contextual insights into the Pekalongan fashion cluster, the findings are limited by their qualitative nature and specific regional focus, which may restrict statistical generalizability to larger industrial contexts. This research offers a novel synthesis of Hsu and Reid’s two-stage decision model with Islamic managerial principles, providing a culturally resonant framework for understanding digital transformation in Muslim-majority regions.